Effect Of Work Overload On Job Satisfaction Through Burnout - Sofia Prima Dewi; Merry Susanti; Sufiyati; Cokki (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
The current study proposes to search the relationship between work overload, burnout, and job satisfaction for lecturers. The questionnaires were distributed among 69 lecturers at the faculty of economics and business using convenience sampling. Data were processed using Partial Least Square-Structural Equation Modelling (PLS-SEM). The finding indicates that work overload has a positive effect on burnout, but work overload and burnout do not have a negative effect on job satisfaction.